Study of clinical outcome in intra articular distal humerus fractures treated with dual plating - Shaik, Riyaz B.; P., Venugopala Reddy; K., Ashok Naidu (International Journal of Research in Medical Sciences, 2017)
Background: In adults, distal humerus fractures are uncommon and intra-articular, oftenly involve both the medial and lateral columns. Open reduction and surgical fixation with plating gives good results. The aim of this study is to evaluate clinical outcome in intra articular distal humerus fractures treated with dual plating. Methods: This is a prospective type of study of 20 cases of supra condylar fracture humerus with inter condylar extension treated surgically with dual plating one on the medial boarder and another on posterior surface of lateral column using standard dorsal approach, olecranon osteotomy. Results: The range of age was between 18-52 years, with mean age of 32.55 years. The maximum incidence was between 18 to 40 years i.e. 16 cases (80%). With road traffic accident (RTA) as major cause of injury. Most of the patients were males 14 (70%) with right upper limb was involved in 12 (60%) cases. According to MEP score clinical outcome was excellent in 4(20%) good in 10(50%) fair in 5(25%) and poor in one (10%). Conclusions: Distal humerus fractures are known for their complex nature and technical difficult in surgical management. Proper anatomical articular reconstruction and stable fixation helps in restoring painless and functional elbow.